Harmful or useful? A case study of the exotic peregrine earthworm morphospecies Pontoscolex corethrurus. (January 2018) - Taheri, S.; Pelosi, C.; Dupont, L.
Abstract: Exotic peregrine earthworms are often considered to cause environmental harm and to have a negative impact on native species, but, as ecosystem engineers, they enhance soil physical properties. Pontoscolex corethrurus is by far the most studied morphospecies and is also the most widespread in tropical areas. The term of morphospecies is used in this review because P. corethrurus may in fact constitute a complex of cryptic species. This earthworm is found in a wide range of habitats, from apparently pristine to any kind of human-disturbed environment. This review synthesizes 265 studies describing the distribution, morphology, biological and ecological traits of this morphospecies, as well as its impacts on soil conditions and communities. We then discuss the characteristics necessary for this specific morphospecies to become a successful colonizer throughout the world and the positive and negative effects it can have on the ecosystems that it has invaded. We emphasize the lack of knowledge of P. corethrurus reproductive mode and ploidy level, of its population genetics, and of the potential existence of cryptic species. To finish, we highlight the fact that data on P. corethrurus interactions with non-earthworm soil macrofauna are scarce. Highlights: Plasticity and r strategy are key traits of P. corethrurus successful invasion. Land use conversion favours the invasibility of soil ecosystems by P. corethrurus. Its positive or negative impacts on the ecosystem depends on soil characteristics. The cryptic diversity of this morphospecies should be studied at worldwide scale.